A review of the removal of heavy metal ions in wastewater by modified montmorillonite. Issue 10 (18th August 2022) - Shi, Yan; Zhong, Songtao; Wang, Xin; Feng, Changping
Abstract: Heavy metal pollution in water environment has always been a hot issue in environmental pollution research. Among various removal methods of heavy metal pollution, adsorption has attracted attention because of its low cost and low secondary pollution. Montmorillonite is one of an ideal adsorption materials because of its natural pore structure and a high specific surface area. In this review, the modification methods of montmorillonite are introduced. The adsorption effect of different heavy metal ions and the main factors affecting the adsorption are discussed in detail. Meanwhile, the adsorption mechanism is intensively reviewed. The removal of Cr(VI), Cd(II), Pb(II), Cu(II), Cs(I), Co(II), Hg(II), Zn(II), Ni(II), and other nine heavy metal ions by modified montmorillonite was summarized and discussed, and the optimal pH values for different adsorbents were also different, but they were all less than 7, and the removal rates of heavy metal ions by modified montmorillonite under optimal conditions were all greater than 90%. It is concluded that the composite montmorillonite material has a great adsorption potential. Finally, it is proposed that the combination of advanced oxidation and composite montmorillonite material adsorption to remove heavy metal ions is an important direction of adsorption and removal of heavy metal ions in the water environment in the future. HIGHLIGHTS: Widely collected the domestic and foreign literature works on the modified adsorption of heavy metals by montmorillonite, and used the methods of analysis and synthesis to identify, classify, merge and study the original literature as a whole. The promising modification direction of montmorillonite and the key points of in-depth research in the removal of heavy metals were put forward. Graphical Abstract